(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
payment system is mechanism for settling financial obligations through the exchange ofvalue. Credit mechanisms are a component of several payment systems, although they are conceptuallydistinct from the rest of the payment process. Banks other financial organizations provide a significantservice in the form of payment systems, which are utilized instead of cash in local and internationaltransactions.Today, payment processors are vital to any successful online business. Customers cancommunicate with online retailers using them. It facilitates monetary transactions between a buyer andseller over the Internet. Many different types of payment gateways are currently available to Indiancustomers.Payment Highway is a payment gateway service that facilitates the use of credit and debitcards for e-commerce purchases.